Prevalence and associated factors of chronic non-communicable diseases among cross-country truck drivers in Ethiopia - Tewodros Yosef (BMC, 2020)
Abstract Background Non-communicable diseases (NCDs) are diseases that are not transmitted from one person to another. Currently, NCDs are the primary causes of morbidity and mortality globally. Truck driving is an occupation that prone drivers to risk factors for NCDs than other occupations. Eventhough risk of developing NCDs among these population is high, studies that showed the prevalence and associated factors of chronic NCDs among truck drivers in Ethiopia are not available. Therefore, this study aimed to assess the prevalence and associated factors of chronic NCDs among truck drivers in Ethiopia. Methods A cross-sectional study was conducted among 422 cross-country truck drivers at the Modjo dry port in Ethiopia. The interviwer-administered questionnaire technique was used to collect the data. The body mass index of the study participants was measured using DHM-15A standardized scale (BMI Height and Weight body fat scale). Results Of the 400 truck drivers interviewed, the prevalence of chronic non-communicable diseases was 28.5, 95% CI (24.1-32.9%). Eighty (20%) had hypertension followed by 32(8%), and 22 (5.5%) had diabetes mellitus and asthma, respectively. The study also found that being married (AOR = 3.14, 95%CI [1.78-5.86]) and Separated/Divorced/Widower (AOR = 2.31, 95% CI [1.12-3.55]), having 3 or more family sizes (AOR = 1.46, 95% CI [1.33-4.42]), BMI ≥ 25 (AOR = 4.66, 95% CI [2.85-7.62]), smoking cigarettes [AOR = 1.71, 95% CI [1.03-2.81]), driving 10 or more years (AOR = 3.48, 95% CI [1.89-5.24]) and driving 9 or more hours daily (AOR = 3.76, 95% CI [1.96-6.54]) were statistically associated with chronic non-communicable diseases. Conclusion The prevalence of chronic NCDs among truck drivers was significant (28.5%), and we can conclude that chronic NCDs are of public health importance among truck drivers in Ethiopia. This may create a substantial load on the healthcare system as an end result of increased demand and contact with healthcare services. Therefore, a rigorous effort is needed to develop strategies for the prevention and management of NCDs.